Association between systemic inflammation response index and female breast cancer based on NHANES data (2001–2018): A cross-sectional study - Liu, Jun; Abisado, Mideth B. (Edelweiss Applied Science and Technology, 2025)
Breast cancer remains the most common malignancy and the leading cause of cancer-related death among women worldwide. Growing evidence implicates systemic inflammation in tumor initiation and progression. The systemic inflammation response index (SIRI), calculated as (neutrophil count * monocyte count) / lymphocyte count (10³/μL), has been proposed as a prognostic biomarker or risk factor in various cancers. Researchers employed statistical association methods among variables, including correlation coefficients, χ² tests, logistic regression, and restricted cubic splines. Using data from 23,045 US women aged ≥20 years in NHANES 2001–2018, the study examined the association between SIRI and female breast cancer prevalence through descriptive statistics, multivariable logistic regression, and subgroup analyses. Women with breast cancer exhibited significantly higher SIRI values than controls, with a dose–response pattern across SIRI quartiles. A one-unit increase in SIRI was associated with a 24% higher odds of breast cancer, and participants in the highest quartile of SIRI had 133% higher breast cancer prevalence compared to those in the lowest quartile [OR = 2.33]. These findings suggest that elevated SIRI is independently associated with prevalent breast cancer in US women and may serve as a practical biomarker for early detection and risk stratification. Additionally, these results may provide important insights into individualized treatment strategies.